A literature review; the role of school counselor on developing spiritual intelligence in the pandemic era (COVID-19): Based on online learning - Izul Haidi Afdilah; Nur Hidayah; Blasius Boli Lasan (Konselor, 2020)
The Covid-19 outbreak that hit the whole world had an impact on changes in life patterns and had an impact on education in particular. Making the teaching and learning process carried out at home, Covid-19 raises psychiatric problems due to information that is not necessarily correct coupled with the discovery of the Covid-19 vaccine and cannot be predicted when it will end. It is feared that students will experience stress, depression, and worry about current conditions coupled with learning patterns that burden new learning tasks. So the role of the BK teacher is needed to provide services that help students to overcome the problems currently faced, with counseling services, information services, and media in counseling. As well as providing assistance to students conducted by School counselor. certainly use media liaison / online such as Zoom, Google Meet, Goole Classroom, and Edmodo. The implementation of giving rocks that are focused on increasing spiritual intelligence because this aspect is the core of the core beliefs of every human being can be sure of life because of the belief about Who Created Everything (Allah), people can be generous because of the promise of alms benefit, people can carry out prayers five times because they have a big principle and are sure of the rewards to be received and people can be good and productive people because a Muslim must be a person who is serious in carrying out his work. The purpose of this study is to provide discourse and idea of the role that can be taken by BK teachers to help overcome the psychiatric problems experienced by students during the Covid-19 pandemic. The method used is the Literature Study. The conclusion is to give a general overview to the teacher guidance and counseling about the roles that can be taken to help alleviate student problems by utilizing the spiritual intelligence of students in the Covid-19 pandemic era by focusing on aspects developed from students, namely Improving Intention, Improving Qolbu Salim, Muhasabah, Personal who are optimistic, and pray.